Potentials and Integrated Suitability Pre-assessment of Wastewater Treatment Plants as Local Energy Cells - Neugebauer, Georg; Lichtenwoehrer, Peter; Huber, Franz; Stoeglehner, Gernot; Kretschmer, Florian (Frontiers in Environmental Science, 2022)
In 2018 the European Union has recognized wastewater as a renewable energy source, particularly due to its thermal energy content. To create and further develop knowledge on the possible role that wastewater could play in the energy transition, this article pursues two objectives: (1) it presents an overview on the (thermal) energy potentials available at the wastewater treatment plants in the Central European area taking their spatial context to adjacent settlement structures into account. (2) It introduces suitability criteria to (pre-)assess the integration of wastewater treatment plants into local energy (heat) supply concepts from an integrated perspective considering energetic, spatial and environmental aspects. The investigations show that there are notable amounts of heat available in close vicinity to potential consumers. Consequently, wastewater treatment plants should be integrated into local heat supply systems as they can play a supportive role in the energy transition towards a renewable and climate friendly future. Herby, the presented suitability criteria support decision makers to identify the most promising wastewater treatment plants in their regional/local specific context by highlighting suitable supply option(s).